Rs11479 in Thymidine Phosphorylase Associated with Prognosis of Patients with Colorectal Cancer Who Received Capecitabine-Based Adjuvant Chemotherapy - Jia X; Zhang T; Sun J; Lin H; Bai T; Qiao Y; Li Y; Li G; Li G; Peng X; Zhang A (Dove Medical Press, 2023)
Xiongjie Jia,* Tao Zhang,* Junjie Sun, Hengxue Lin, Tianliang Bai, Yating Qiao, Yaxin Li, Gang Li, Guicun Li, Xinyu Peng, Aimin Zhang Department of Gastrointestinal Surgery, Affiliated Hospital of Hebei University, Baoding, People's Republic of China*These authors contributed equally to this workCorrespondence: Aimin Zhang; Xinyu Peng, Department of Gastrointestinal Surgery, Affiliated Hospital of Hebei University, No. 212 Yu-Hua East Road, Baoding City, Hebei Province, People's Republic of China, Tel +863125983782, Email hdfyzam@126.com; pengxinyu_2012@163.comObjective: Thymidine Phosphorylase (TYMP) gene was of potential significance in the process of colorectal cancer (CRC) development and played an important role in capecitabine metabolism. This study was to identify the association between TYMP polymorphism and prognosis of postoperative patients with CRC who received capecitabine-based adjuvant chemotherapy.Methods: A total of 218 patients with CRC who were treated with surgical resection and capecitabine-based adjuvant chemotherapy were included in this study retrospectively. Peripheral blood and peripheral blood mononuclear cell (PBMC) specimen of the patients were collected for the genotyping of TYMP polymorphism and TYMP mRNA expression, respectively. Univariate analysis of genotypes and prognosis was carried out by Kaplan-Meier survival analysis, Cox regression analysis was adopted in multivariate analysis. The mRNA expression of TYMP according to genotype status was analyzed using non-parameter test.Results: Prevalence of rs11479 in TYMP among the 218 patients exhibited that minor allele frequency of rs11479 was 0.20 (GG 141 cases, GA 68 cases and AA 9 cases), which was in accordance with Hardy-Weinberg equilibrium (P=0.825). Association analysis suggested that the median disease-free survival (DFS) of patients with GG genotype and GA/AA genotype was 3.1 and 6.1 years, respectively (P=0.004). Furthermore, the median overall survival of patients with GG genotype and GA/AA genotype was 5.0 and 7.0 years, respectively (P=0.033). Multivariate Cox regression analysis exhibited that rs11479 polymorphism was an independent factor for DFS (HR = 1.64, P=0.009). Additionally, of the 65 PBMC specimens, mRNA expression results indicated that patients with GA/AA genotypes conferred significantly higher mRNA expression of TYMP than that of patients with GG genotype (P< 0.001).Conclusion: Polymorphism rs11479 in TYMP gene might predict the prognosis of patients with CRC who received capecitabine-based adjuvant chemotherapy through mediation of the mRNA expression of TYMP. The conclusion of this study should be validated in prospective clinical trials subsequently.Keywords: colorectal cancer, adjuvant chemotherapy, capecitabine, prognosis, polymorphism